Intra-Lagos migration and spread of COVID-19: revisiting the structural vulnerability theory - Johnson Oluwole Ayodele; Oluwagbemiga Adeyemi; Jane Roli Adebusuyi (Cogent Social Sciences, 2024)
AbstractThis article reviews how the intra-Lagos migration and routinized lifestyle activities of residents impact the spread of COVID-19 in the context of structural vulnerability theory. This study collected data from 32 purposively selected in-depth interview participants using a qualitative method. The data were thematically and content analyzed. It found that the lockdown worked between 6:00 am and 6:00 pm daily at night, social community replaced social distancing. The participants, who lived on daily incomes without palliatives, embarked more on intra-Lagos migration in defiance of the lockdown to justify the assumptions of structural vulnerability theory. The study concludes that the government should impose a dusk-to-dawn curfew to prevent night migration-induced infection in Lagos if a future pandemic occurs. The Ministry of Education should monitor Lagos communities to protect vulnerable children from the threat of infections. Moreover, public policy should improve the capacity of children to display the appropriate forms of lifestyle and routine activities that discourage careless infection-spreading migration as a means of promoting solidarity for public health in Lagos. In readiness for future epidemics, the article suggests a probe of the handlers of the distribution of the COVID-19 palliatives that caused residents to throng the streets of Lagos and Nigeria for food.